Effect of carbon-negative aggregates on the strength properties of concrete for permeable pavements. Issue 14 (5th December 2020) - Monrose, John; Tota-Maharaj, K.; Mwasha, A.; Hills, C.
ABSTRACT: Permeable pavements are engineered to temporarily store water to reduce flooding during rainfall events. Permeable pavements are distinguished primarily based on their surface materials which can vary from concrete, asphalt, clay brick, concrete pavers or plastic grids. This paper examined the effect of lightweight carbon-negative aggregates (CNA) on the behaviour of concrete intended for use as solid concrete block pavers in permeable pavements. Performance indicators targeted compressive strength, splitting tensile strength, density and water absorption. CNA were produced and sourced from manufacturing firm Carbon8 Systems in Kent U.K which applies patented accelerated carbonation technology to solidify incinerated ash into useful eco-friendly aggregates. The methodology involved substituting natural aggregates (NA) by mass, with CNA at percentages varying from 0 to 100. A scanning electron microscope was used to examine the aggregate–mortar interface. Both the compressive and tensile strengths decreased exponentially with the addition of CNA. Average 28-day compressive and splitting tensile strengths ranged from 69 MPa (10, 000 PSI) to 18 MPa (2600 PSI) and 3.84 MPa (560 PSI) to 1.23 MPa (178 PSI) respectively. Density values decreased linearly with the addtion of CNA with average values ranging from 2200–2600 kg/m 3 . ⁠Conversely, water absorption increased with increases in CNA with average values ranging from 1.66% to 9.17%. Depending on the loading requirements, CNA can replace NA in solid permeable pavement blocks by up to 100%.